PERSONAL FINANCIAL MANAGEMENT NEEDS OF SOCIAL WORKERS AND YOUNG PEOPLE AT RISK - Vintere, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Social exclusion is widely recognized as having a lasting negative impact on quality of life and future opportunities. Many young people live in families at risk of poverty. One of the causes of social exclusion is the inability to manage personal finances. Social workers working with these young people may not always be able to help, as they often do not have sufficient knowledge on how to properly consult young people on their personal financial issues. In order to find out the needs of personal financial management, a case study involving social workers and young people from social exclusion groups was carried out with the financial support of Nordplus Horizontal programme. This article analyses data from a Latvian survey that reveals main reasons causing personal financial management problems, as well as ways to overcome them. The study also answers the question of what knowledge and skills, as well as methodological materials, are needed by social workers to support young people at risk and to develop their personal financial management skills.